2024
DOI: 10.1590/1678-9199-jvatitd-2023-0042
|View full text |Cite
|
Sign up to set email alerts
|

Skin secretions of Leptodactylidae (Anura) and their potential applications

Juan F. C. Carrillo,
Amanda Galdi Boaretto,
Diego J. Santana
et al.

Abstract: The skin of anuran species is a protective barrier against predators and pathogens, showing also chemical defense by substances that represent a potential source for bioactive substances. This review describes the current chemical and biological knowledge from the skin secretions of Leptodactylidae species, one of the most diverse neotropical frog families. These skin secretions reveal a variety of substances such as amines (12), neuropeptides (16), and antimicrobial peptides (72). The amines include histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…There are more than forty ocellatins described in the literature, and these peptides are the most abundant peptides found in the skin secretions of Leptodactylidae [10,12]. Glycine is a recurrent amino acid in multiple positions of these peptides [10], which can be observed in the ocellatin-VT from L. vastus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are more than forty ocellatins described in the literature, and these peptides are the most abundant peptides found in the skin secretions of Leptodactylidae [10,12]. Glycine is a recurrent amino acid in multiple positions of these peptides [10], which can be observed in the ocellatin-VT from L. vastus.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than forty ocellatins described in the literature, and these peptides are the most abundant peptides found in the skin secretions of Leptodactylidae [10,12]. Glycine is a recurrent amino acid in multiple positions of these peptides [10], which can be observed in the ocellatin-VT from L. vastus. Carrillo et al [10] also observed that leucine and lysine are often present, which also occurs in ocellatin-VT: leucine appears in five positions while there are four lysine residues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations